2005
DOI: 10.1097/01.tp.0000164159.20075.16
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Rabbit Antithymocyte Globulin Triggers B-Cell and Plasma Cell Apoptosis by Multiple Pathways

Abstract: Polyclonal rATG induces complement-independent apoptosis of naive, activated, and plasma B cells. This effect appears to involve the caspase- and cathepsin-mediated apoptosis pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
172
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(181 citation statements)
references
References 43 publications
6
172
2
1
Order By: Relevance
“…ATG also induces B-cell depletion. 24 Interestingly, even when the effect of B cells on atherosclerosis is subset dependent, B-cell depletion has been associated with atherosclerosis progression. 25 Compelling data from both animal models and other human populations suggest CD8 + activation as the trigger of ATG-induced atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…ATG also induces B-cell depletion. 24 Interestingly, even when the effect of B cells on atherosclerosis is subset dependent, B-cell depletion has been associated with atherosclerosis progression. 25 Compelling data from both animal models and other human populations suggest CD8 + activation as the trigger of ATG-induced atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, because certain epitopes are shared between T and B cells and because pediatric thymi also contain CD20 + B cells and CD138 + plasma cells, ATG contain IgGs directed against these latter subsets. 39 As a result, in vitro studies have shown that ATG induces apoptosis of naive, activated B cells and bone marrow resident plasma cells at clinically relevant concentrations (1-100 ng/ml). 39 However, the importance of ATGinduced plasma and/or B cell depletion in vivo has not been clearly shown.…”
Section: Effect Of Induction Therapy On Dndsa Generationmentioning
confidence: 99%
“…Later in the study, cohort 2 also received a 4-day course of anti-thymocyte globulin (ATG), which is the purified immunoglobulin (Ig)G fraction of rabbits or horses that are immunized with human thymocytes or T cell lines. ATG depletes peripheral lymphocytes through complement-dependent lysis or activation-associated apoptosis [13][14][15]. ATG formulations have been used in human transplantation for decades [16].…”
Section: Introductionmentioning
confidence: 99%